The Authority of Prosecutors in Handling Cases Involved by Children Who Commit Repeated Crimes - Larasati, Galuh; Suwondo, Denny (UNISSULA Semarang, 2025)
Recidivist or Repeat Offender refers to a situation where a person commits multiple offenses or more after having been sentenced by a judge. When associated with children, the term